Composite solid electrolyte as well as preparation method and application thereof

The organic-inorganic cross-linking network is constructed through the reaction of isocyanate compounds and polyethylene glycol, and the inorganic-organic interface of composite solid electrolytes is optimized, which solves the problems of low conductivity and poor interface stability, significantly improves the transmission speed of lithium ions and Cycling performance of the battery.

CN119315093AActive Publication Date: 2025-01-14CHINA FAW CO LTD +1

Patent Information

Application Number
CN202411362209.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-14
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

Inadequate inorganic-organic interactions in composite solid electrolytes lead to low conductivity, poor dispersion and poor interface stability, which affects the migration of lithium ions and the cycling performance of the battery.

Method used

Using isocyanate compounds as crosslinking agents, the organic-inorganic hybrid crosslinking network is constructed through the nucleophilic addition reaction between inorganic solid electrolyte and polyethylene glycol, and the inorganic-organic interface compatibility is optimized, and the composite is prepared through heat treatment steps. Solid electrolyte.

Benefits of technology

It improves room temperature conductivity and interface contact stability, enhances the transmission speed and electrochemical window of lithium ions, and improves the cycle performance and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315093A_ABST
    Figure CN119315093A_ABST
Patent Text Reader

Abstract

The invention provides a composite solid electrolyte as well as a preparation method and application thereof, and relates to the technical field of lithium ion batteries. Specifically, the composite solid electrolyte is prepared from the following components in parts by weight: 10-20 parts of an inorganic solid electrolyte, 10-20 parts of polyethylene glycol, 10-20 parts of polyoxyethylene, 1-3 parts of a cross-linking agent, 10-20 parts of lithium salt and a plurality of solvents, wherein the cross-linking agent comprises an isocyanate compound. According to the invention, the cross-linking agent containing the isocyanate group, the inorganic solid electrolyte and the polyethylene glycol are subjected to nucleophilic addition reaction, so that the inorganic solid electrolyte is skillfully connected with the polyethylene glycol through chemical bonds, and an organic-inorganic interface is further optimized; the organic-inorganic composite solid electrolyte disclosed by the invention has good ion transport property and a relatively wide electrochemical window, and the cycle performance and the rate capability of a lithium battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite solid electrolyte and a preparation method and application thereof. Background Art

[0002] With the increasing number of electronic devices and electric vehicles, battery workers have extensively studied solid-state lithium batteries with high energy density, good flexibility and high safety to meet consumer needs. Solid-state lithium batteries are considered to be one of the most promising next-generation lithium battery technologies. With the continuous breakthroughs in technology and the reduction of large-scale production costs, solid-state lithium batteries have significant advantages in safety, energy density, cycle life, etc., and their industrialization process is expected to accelerate; however, solid-state lithium battery technology still faces many bottlenecks, such as the selection of electrolyte materials, solid-solid interface contact, fast charging performance, etc.

[0003] Solid-state lithium batteries are divided into all-solid-state and semi-solid-state batteries, and the solid electrolytes involved mainly include oxide electrolytes, sulfide electrolytes, polymer electrolytes, or composite electrolytes of any composition. Compared with polymer electrolytes or inorganic solid electrolytes, organic-inorganic composite solid electrolytes can well balance the electrochemical properties of inorganic electrolytes and the mechanical properties of polymer electrolytes through the synergistic effect between the components, and well inhibit the dendrite growth of lithium metal electrodes during the charge and discharge process.

[0004] However, composite solid electrolytes still have the following problems: First, the weak organic-inorganic interaction in the composite solid electrolyte leads to phase separation and uneven dispersion of inorganic nanoparticles in the composite solid electrolyte, which hinders the migration of lithium ions around the interphase and reduces the ionic conductivity; second, lithium ions are easily deposited at the organic-inorganic interface and form lithium dendrites, which continue to diffuse in the composite solid electrolyte and eventually lead to a short circuit in the battery. Therefore, from the above defects, it can be seen that strengthening the organic-inorganic interaction in the composite solid electrolyte and improving the affinity between the phases are key factors in enhancing the electrochemical performance of the composite solid electrolyte.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide a composite solid electrolyte, aiming to optimize the organic-inorganic interface compatibility of the organic-inorganic composite solid electrolyte and solve the defects of conventional composite solid electrolytes such as low conductivity, poor dispersibility, and poor organic-inorganic interface stability.

[0007] The second object of the present invention is to provide a method for preparing the composite solid electrolyte, which is simple and easy, has mild conditions, low cost, and can meet the needs of mass production.

[0008] A third object of the present invention is to provide a lithium ion battery.

[0009] A fourth object of the present invention is to provide an electrical device.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A composite solid electrolyte is prepared by including the following components by weight: 10-20 parts of inorganic solid electrolyte, 10-20 parts of polyethylene glycol, 10-20 parts of polyethylene oxide, 1-3 parts of cross-linking agent, 10-20 parts of lithium salt and some solvent;

[0012] Wherein, the cross-linking agent includes isocyanate compounds.

[0013] A method for preparing the composite solid electrolyte comprises the following steps:

[0014] A uniform suspension containing an inorganic solid electrolyte is prepared, and then a cross-linking agent is added to perform a first heat treatment; after the first heat treatment is completed, polyethylene glycol is added to perform a second heat treatment; after the first heat treatment is completed, polyethylene oxide and a lithium salt are added to perform a third heat treatment to obtain a composite slurry;

[0015] The composite slurry is coated on a support plate, and the support plate is peeled off after drying to obtain a composite solid electrolyte.

[0016] A lithium ion battery comprises the composite solid electrolyte.

[0017] An electrical device comprises the lithium-ion battery.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides a composite solid electrolyte that optimizes the organic-inorganic compatibility in a solid electrolyte based on isocyanate compounds, and has outstanding effects such as high conductivity at room temperature and stable interface contact. Specifically, the present invention uses a cross-linking agent containing a specific group (isocyanate group), an inorganic solid electrolyte and polyethylene glycol to undergo a nucleophilic addition reaction, so that the inorganic solid electrolyte can be cleverly linked to the polyethylene glycol through a chemical bond through the isocyanate group, thereby optimizing the interface between organic and inorganic; the hydroxyl group on the surface of the inorganic solid electrolyte will undergo an addition reaction with the isocyanate group to generate a carbamate, thereby constructing an organic-inorganic hybrid cross-linked network between the inorganic solid electrolyte, the isocyanate group and the polyethylene glycol.

[0020] In the present invention, the inorganic solid electrolyte has good ion transportability and a wide electrochemical window, which not only accelerates the transmission speed of lithium ions but also effectively improves the electrochemical window, improves the conductivity of the room temperature electrolyte membrane without reducing the mechanical properties of the membrane, and makes the electrolyte membrane have good interface compatibility with the lithium metal negative electrode, optimizes the impedance of the organic-inorganic interface, thereby improving the cycle performance and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 TEM image of LLZTO@TDI of the comparative example of the present invention;

[0023] Figure 2 TEM image of LLZTO@TDI of the comparative example of the present invention;

[0024] Figure 3 The infrared spectra of the composite solid electrolyte (F-30) prepared in Example 1 of the present invention, LLZTO@TDI of the reference example, paraphenylene diisocyanate (TDI), polyethylene oxide (PEO) and polyethylene glycol (PEG);

[0025] Figure 4 is the XRD diagram of an embodiment of the present invention; wherein, Figure 4 (a) provides the XRD patterns of LLZTO@TDI and LLZTO as control examples. Figure 4 (b) provides XRD patterns of the composite solid electrolytes of Examples 1 to 4 and the comparative example;

[0026] Figure 5 is a graph showing the change in ionic conductivity of the composite solid electrolyte according to an embodiment of the present invention as a function of temperature;

[0027] Figure 6 This is a test diagram of the electrical performance of the button cell prepared in Example 1 of the present invention; Figure 6 (a) provides a room temperature cycle test diagram of a button cell. Figure 6 (b) provides the charge and discharge curves of each cycle number at 0.1C;

[0028] Figure 7 This is a cycle stability test curve of the symmetrical battery prepared in Example 1 of the present invention; Figure 7(a) provides the variation curves of positive and negative voltages during 2300 h of symmetrical battery cycling. Figure 7 (b) provides the change curves of positive and negative voltages of the symmetrical battery during the cycle of 2000h to 2010h. DETAILED DESCRIPTION

[0029] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.

[0030] The first aspect of the present invention is to provide a composite solid electrolyte, which is prepared by including the following components in parts by weight: 10 to 20 parts of an inorganic solid electrolyte, 10 to 20 parts of polyethylene glycol, 10 to 20 parts of polyethylene oxide, 1 to 3 parts of a cross-linking agent, 10 to 20 parts of a lithium salt and a number of solvents; wherein the cross-linking agent includes an isocyanate compound.

[0031] As a preferred embodiment, the inorganic solid electrolyte includes LLZO, Li 10 GeP2S 12 , LLZTO and Li3YBr6; in some more preferred embodiments, the inorganic solid electrolyte.

[0032] In the present invention, the inorganic solid electrolyte not only accelerates the transmission of lithium ions but also has a wider electrochemical window. Without reducing the mechanical properties of the electrolyte membrane layer, it improves the conductivity of the electrolyte membrane at room temperature, optimizes the interface of the organic-inorganic solid electrolyte, reduces the impedance of the interface, and thus improves the cycle performance and rate performance of the battery.

[0033] As a preferred embodiment, the molecular weight of the polyethylene glycol is 400 to 4000. As a more preferred embodiment, the molecular weight of the polyethylene glycol is 400 to 2000, including but not limited to any one of 400, 500, 600, 700, 800, 900, 1000, 1200, 1400, 1500, 1600, 1800, 2000 or a numerical range consisting of any two. In the present invention, the role of the polyethylene glycol is to transport lithium ions and improve the mechanical properties of the composite solid-state electrolyte.

[0034] As a preferred embodiment, the molecular weight of the polyethylene oxide is 10 5 ~2*10 6 , including but not limited to 0.1*10 6 , 0.2*10 6 , 0.5*10 6 , 0.8*10 6 , 1*10 6 , 1.2*10 6 , 1.5*10 6 , 1.8*10 6 , 1.9*10 6 , 2*10 6 As a more preferred embodiment, the molecular weight of the polyethylene oxide is 9*10 5 ~1.5*10 6 The role of the polyethylene oxide in the present invention is to transport lithium ions and improve the mechanical properties (mainly toughness) of the composite solid electrolyte; but it is worth noting that by controlling the addition amount of the inorganic solid electrolyte, isocyanate group and polyethylene glycol participating in the reaction in the present invention, the polyethylene oxide basically does not participate in the addition reaction; the polyethylene oxide thus obtained is interspersed in the organic-inorganic hybrid cross-linked network in the composite solid electrolyte in a linear structure.

[0035] As a preferred embodiment, the isocyanate compound includes at least one of 1,3-phenylene diisocyanate, p-phenylene diisocyanate and 3,5-dinitroisocyanate. The present invention uses a specific cross-linking agent, which functions to optimize the interface between organic and inorganic through a nucleophilic addition reaction between the hydroxyl group of polyethylene glycol, LLZTO and the isocyanate group of the cross-linking agent.

[0036] As a preferred embodiment, the lithium salt includes at least one of LiPF6, LiClO4, LiTFSI, LiFSI, LiBOB and LiDFOB. In the present invention, the lithium salt provides lithium ions and reduces the glass transition temperature of the polymer electrolyte.

[0037] In the present invention, when the inorganic solid electrolyte, the isocyanate compound, and the lithium salt are selected from two or more of the above specific options, the present invention does not have any special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio.

[0038] As a preferred embodiment, the solvent includes one or more of N,N-dimethylformamide, benzene, toluene, tetrahydrofuran, acetonitrile, dimethyl sulfoxide or N-methylpyrrolidone; when the organic solvent is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In some more preferred embodiments, the weight parts of the solvent are 300 to 350 parts.

[0039] As a preferred embodiment, the composite solid electrolyte is prepared by including the following components in parts by weight: 12 to 16 parts of inorganic solid electrolyte, 11 to 16 parts of polyethylene glycol, 11 to 16 parts of polyethylene oxide, 1 to 2 parts of cross-linking agent, 10 to 15 parts of lithium salt and 310 to 340 parts of solvent.

[0040] As a more preferred embodiment, the composite solid electrolyte is prepared by including the following components in parts by weight: 12 to 13 parts of inorganic solid electrolyte, 12 to 13 parts of polyethylene glycol, 12 to 13 parts of polyethylene oxide, 1 to 1.5 parts of cross-linking agent, 11 to 13 parts of lithium salt and 310 to 330 parts of solvent.

[0041] As a preferred implementation, the composite solid electrolyte is in a thin film state, and the thickness of the composite solid electrolyte is 100 μm to 150 μm.

[0042] The second aspect of the present invention is to provide a method for preparing the composite solid electrolyte.

[0043] (1) Preparation of organic-inorganic composite reaction slurry: prepare a uniform suspension containing an inorganic solid electrolyte, then add a cross-linking agent and perform a first heat treatment; after the suspension is completed, add polyethylene glycol and perform a second heat treatment; after the suspension is completed, add polyethylene oxide and lithium salt and perform a third heat treatment to obtain a composite slurry.

[0044] As a preferred embodiment, during the preparation of the suspension, one or more means including stirring, oscillation, ultrasound, centrifugation, etc. are used to achieve sufficient dispersion of the inorganic solid electrolyte; in some more preferred embodiments, the solution containing the inorganic solid electrolyte is ultrasonically treated at room temperature for 1h to 2h to obtain the suspension.

[0045] As a preferred embodiment, the temperature of the first heat treatment is 40° C. to 80° C., and the time of the first heat treatment is 2 h to 10 h.

[0046] As a preferred embodiment, the temperature of the second heat treatment is 40°C to 80°C, and the time of the second heat treatment is 2h to 10h.

[0047] As a preferred embodiment, the temperature of the third heat treatment is 40° C. to 80° C., and the time of the third heat treatment is 20 h to 40 h.

[0048] As a preferred embodiment, during the addition process of the cross-linking agent, the polyethylene glycol, the polyethylene oxide and the lithium salt and any heat treatment process, the reaction solution is in a stirring state; in some more preferred embodiments, the stirring frequency is 50rpm to 5000rpm.

[0049] As a more preferred embodiment, before adding the cross-linking agent, the polyethylene glycol, the polyethylene oxide and the lithium salt, the solution of the cross-linking agent, the solution of the polyethylene glycol, the polyethylene oxide and the lithium salt are separately prepared in advance to ensure that each raw material component is fully dispersed in the reaction solution.

[0050] (2) Slurry molding treatment: The composite slurry is coated on a support plate, and the support plate is peeled off after drying to obtain a composite solid electrolyte.

[0051] As a preferred embodiment, the coating is performed by one of roller coating, extrusion coating or blade coating; in some more preferred embodiments, a grooved blade or a gravure blade is used to scrape the composite slurry onto the surface of the support plate, and the shape or area of ​​the support plate can be used to control the shape of the composite solid electrolyte, and the support plate is selected from any polymer material plate or film, etc.

[0052] As a preferred implementation, the drying temperature is 50° C. to 80° C., and the drying time is 20 h to 40 h.

[0053] As a preferred embodiment, the drying is carried out in a vacuum atmosphere.

[0054] The operating method steps and the containers or equipment used in the present invention can be implemented according to conventional processing means of those skilled in the art, except for the above-mentioned limitations and preferred embodiments, and the present invention does not impose any other limitations thereon.

[0055] A third aspect of the present invention is to provide a lithium ion battery.

[0056] The lithium-ion battery includes the composite solid electrolyte. It is understandable that the lithium-ion battery belongs to a solid-state lithium battery or a semi-solid-state lithium battery; in addition to the composite solid electrolyte, the lithium-ion battery should include electrodes and other necessary or unnecessary functional elements or packaging components, etc., which can be arbitrarily selected and combined by those skilled in the art; when the composite solid electrolyte of the present invention is included in the lithium-ion battery, whether or not other electrolyte functional components are used in the lithium-ion battery, it can be regarded as an embodiment of the present invention.

[0057] As a more preferred embodiment, the electrode includes a positive electrode and a negative electrode; wherein the positive electrode includes a positive electrode active material, a current collector, a conductive agent and a binder, and the mass ratio thereof is preferably 8:1:1, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganate, lithium iron phosphate and lithium iron manganese phosphate, the current collector includes copper foil or aluminum foil, the conductive agent includes at least one of acetylene black, Ketjen black and carbon nanotubes, and the binder includes at least one of polytetrafluoroethylene, polyurethane and polyvinylidene fluoride; in addition, the negative electrode is metallic lithium. The present invention has no special requirements for the assembly method of the lithium ion battery, and an assembly method familiar to those skilled in the art can be used.

[0058] A fourth aspect of the present invention is to provide an electrical device.

[0059] The electrical equipment includes the lithium-ion battery. In some optional embodiments, the electrical equipment can be any equipment or device that relies on electric energy to work or operate, including but not limited to new energy vehicles, building electrical equipment, industrial electrical appliances, household and agricultural electrical appliances, etc.; when the lithium-ion battery is included, any electrical equipment equipped with the lithium-ion battery can belong to an embodiment of the present invention.

[0060] Example 1

[0061] Under nitrogen atmosphere, 0.174 g of LLZTO was dispersed in 3 mL of N,N-dimethylformamide and ultrasonicated at room temperature for 1 h to obtain a uniform suspension;

[0062] A solution of N,N-dimethylformamide (1 mL) containing 0.016 g of p-phenylene diisocyanate was added to the above suspension, and the mixture was stirred at 80°C for 5 h;

[0063] Then, a solution of N,N-dimethylformamide (1 mL) containing 0.2 g of polyethylene glycol (molecular weight 2000) was added to the above solution, and heating was continued at 80 °C for 10 h;

[0064] Finally, 0.2 g of polyethylene oxide (molecular weight 100w) and 0.167 g of LiTFSI were added to the above solution, and the temperature was adjusted to 40 °C and heated and stirred for 24 h to obtain a viscous liquid;

[0065] The viscous liquid was coated on a rectangular polytetrafluoroethylene plate of 10×20×2 (cm) with a scraper, dried in a vacuum oven at 60° C. for 24 h, and the film was peeled off to obtain the composite solid electrolyte of this embodiment.

[0066] Example 2

[0067] Under nitrogen atmosphere, 0.044 g of LLZTO was dispersed in 3 mL of N,N-dimethylformamide and ultrasonicated at room temperature for 1 h to obtain a uniform suspension;

[0068] A solution of N,N-dimethylformamide (1 mL) containing 0.016 g of p-phenylene diisocyanate was added to the above suspension, and the mixture was stirred at 40°C for 10 h;

[0069] Then, a solution of N,N-dimethylformamide (1 mL) containing 0.2 g of polyethylene glycol was added to the above solution, and heating was continued at 40 °C for 10 h;

[0070] Finally, 0.2 g of polyethylene oxide and 0.167 g of LiTFSI were added to the above solution, and the temperature was adjusted to 40 °C and heated with stirring for 30 h to obtain a viscous liquid;

[0071] The viscous liquid was coated on a rectangular polytetrafluoroethylene plate of 10×20×2 (cm) with a scraper, dried in a vacuum oven at 60° C. for 24 h, and the film was peeled off to obtain the composite solid electrolyte of this embodiment.

[0072] Example 3

[0073] Under nitrogen atmosphere, 0.1 g of LLZTO was dispersed in 3 mL of N,N-dimethylformamide and ultrasonicated at room temperature for 1 h to obtain a uniform suspension;

[0074] A solution of N,N-dimethylformamide (1 mL) containing 0.016 g of p-phenylene diisocyanate was added to the above suspension, and the mixture was stirred at 80°C for 5 h;

[0075] Then, a solution of N,N-dimethylformamide (1 mL) containing 0.2 g of polyethylene glycol was added to the above solution, and heating was continued at 80 °C for 5 h;

[0076] Finally, 0.2 g of polyethylene oxide and 0.167 g of LiTFSI were added to the above solution, and the temperature was adjusted to 80 °C and heated with stirring for 20 h to obtain a viscous liquid;

[0077] The viscous liquid was coated on a rectangular polytetrafluoroethylene plate of 10×20×2 (cm) with a scraper, dried in a vacuum oven at 60° C. for 24 h, and the film was peeled off to obtain the composite solid electrolyte of this embodiment.

[0078] Example 4

[0079] Under nitrogen atmosphere, 0.267 g of LLZTO was dispersed in 3 mL of N,N-dimethylformamide and ultrasonicated at room temperature for 1 h to obtain a uniform suspension;

[0080] A solution of N,N-dimethylformamide (1 mL) containing 0.016 g of p-phenylene diisocyanate was added to the above suspension, and the mixture was stirred at 80°C for 5 h;

[0081] Then, a solution of N,N-dimethylformamide (1 mL) containing 0.2 g of polyethylene glycol was added to the above solution, and heating was continued at 80 °C for 10 h;

[0082] Finally, 0.2 g of polyethylene oxide and 0.167 g of LiTFSI were added to the above solution, and the temperature was adjusted to 40 °C and heated with stirring for 24 h to obtain a viscous liquid;

[0083] The viscous liquid was coated on a rectangular polytetrafluoroethylene plate of 10×20×2 (cm) with a scraper, dried in a vacuum oven at 80° C. for 20 h, and the film was peeled off to obtain the composite solid electrolyte of this embodiment.

[0084] Example 5

[0085] Under nitrogen atmosphere, 0.174 g of LLZTO was dispersed in 3 mL of N,N-dimethylformamide and ultrasonicated at room temperature for 1 h to obtain a uniform suspension;

[0086] A solution of N,N-dimethylformamide (1 mL) containing 0.016 g of p-phenylene diisocyanate was added to the above suspension, and the mixture was stirred at 80°C for 5 h;

[0087] Then, a solution of N,N-dimethylformamide (1 mL) containing 0.3 g of polyethylene glycol was added to the above solution, and heating was continued at 80 °C for 10 h;

[0088] Finally, 0.1 g of polyethylene oxide and 0.167 g of LiTFSI were added to the above solution, and the temperature was adjusted to 40 °C and heated with stirring for 24 h to obtain a viscous liquid;

[0089] The viscous liquid was coated on a rectangular polytetrafluoroethylene plate of 10×20×2 (cm) with a scraper, dried in a vacuum oven at 60° C. for 24 h, and the film was peeled off to obtain the composite solid electrolyte of this embodiment.

[0090] Example 6

[0091] Under nitrogen atmosphere, 0.174 g of LLZO was dispersed in 3 mL of N,N-dimethylformamide and sonicated at room temperature for 1 h to obtain a uniform suspension;

[0092] A solution of N,N-dimethylformamide (1 mL) containing 0.016 g of 1,3-phenylene diisocyanate was added to the above suspension, and the mixture was stirred at 80°C for 5 h;

[0093] Then, a solution of N,N-dimethylformamide (1 mL) containing 0.2 g of polyethylene glycol was added to the above solution, and heating was continued at 80 °C for 10 h;

[0094] Finally, 0.2 g of polyethylene oxide and 0.167 g of lithium salt (LiPF6 and LiFSI, mass ratio 1:1) were added to the above solution, and the temperature was adjusted to 40 °C and heated and stirred for 24 h to obtain a viscous liquid;

[0095] The viscous liquid was coated on a rectangular polytetrafluoroethylene plate of 10×20×2 (cm) with a scraper, dried in a vacuum oven at 60° C. for 24 h, and the film was peeled off to obtain the composite solid electrolyte of this embodiment.

[0096] Example 7

[0097] Under nitrogen atmosphere, 0.174 g of Li3YBr6 was dispersed in 3 mL of N,N-dimethylformamide and ultrasonicated at room temperature for 1 h to obtain a uniform suspension;

[0098] A solution of N,N-dimethylformamide (1 mL) containing 0.016 g of 3,5-dinitroisocyanate was added to the above suspension, and the mixture was stirred at 80° C. for 5 h;

[0099] Then, a solution of N,N-dimethylformamide (1 mL) containing 0.2 g of polyethylene glycol was added to the above solution, and heating was continued at 80 °C for 10 h;

[0100] Finally, 0.2 g of polyethylene oxide and 0.167 g of lithium salt (LiTFSI and LiDFOB, mass ratio 1:1) were added to the above solution, and the temperature was adjusted to 40 °C and heated with stirring for 24 h to obtain a viscous liquid;

[0101] The viscous liquid was coated on a rectangular polytetrafluoroethylene plate of 10×20×2 (cm) with a scraper, dried in a vacuum oven at 60° C. for 24 h, and the film was peeled off to obtain the composite solid electrolyte of this embodiment.

[0102] Comparison example

[0103] Under nitrogen atmosphere, 0.174 g of LLZTO was dispersed in 3 mL of N,N-dimethylformamide and ultrasonicated at room temperature for 1 h to obtain a uniform suspension;

[0104] A solution of N,N-dimethylformamide (1 mL) containing 0.016 g of p-phenylene diisocyanate was added to the above suspension, and the mixture was stirred at 80°C for 5 h;

[0105] The obtained product was washed with N,N-dimethylformamide and centrifuged several times, dried in a vacuum oven at 60°C for 24 hours, and the film was removed to obtain the solid product LLZTO@TDI of this reference example.

[0106] like Figure 1 , Figure 2 The transmission electron microscope (TEM) image of LLZTO@TDI in the control example is shown in FIG. Figure 1 , Figure 2 It can be seen that a nucleophilic addition reaction occurs between p-phenylene diisocyanate and the hydroxyl group of LLZTO, indicating that LLZTO and polyethylene glycol can be cleverly linked together through chemical bonds via the isocyanate group.

[0107] like Figure 3 The figure shows the infrared spectra of the composite solid electrolyte (F-30) prepared in Example 1, LLZTO@TDI of the control example, paraphenylene diisocyanate (TDI), polyethylene oxide (PEO) and polyethylene glycol (PEG); Figure 3 It can be seen that in the infrared spectrum of p-phenylene diisocyanate, at 2270cm -1 The characteristic absorption peak of isocyanate group (-NCO) is at 1521cm. However, the characteristic peak of -NCO disappears in the infrared spectrum of LLZTO@TDI, and a new -NH (1521cm -1 )、-C=O(1657cm -1 ) absorption band appears; indicating that hydroxyl and isocyanate undergo esterification reaction; further, in the infrared spectrum of the composite solid electrolyte F-30, at 3433cm -1 The stretching vibration peak of -OH is at 1099cm -1 is the stretching vibration peak of COC, indicating that polyethylene glycol was successfully grafted onto the LLZTO surface through p-phenylene diisocyanate.

[0108] like Figure 4 As shown, Figure 4 (a) provides X-ray diffraction (XRD) spectra of LLZTO@TDI and LLZTO of the control example, wherein the "80-0457" curve corresponds to the data standard card curve of the XRD of LLZTO; Figure 4(b) provides X-ray diffraction (XRD) spectra of the composite solid electrolyte (F-30) corresponding to Example 1, the composite solid electrolyte (F-10) corresponding to Example 2, the composite solid electrolyte (F-20) corresponding to Example 3, the composite solid electrolyte (F-40) corresponding to Example 4, and LLZTO@TDI (F-0) corresponding to the control example; Figure 4 It can be seen that there is no obvious difference between LLZTO@TDI and LLZTO in XRD, which indicates that LLZTO can still maintain its original crystal structure during the surface modification process. Figure 4 (b) It can be seen from the comparison that compared with pure organic polymer, the embedding of LLZTO reduces the crystallinity of the polymer electrolyte, indicating that the amorphous phase area in the polymer electrolyte increases, thereby improving the ionic conductivity.

[0109] like Figure 5 The figure provides a curve diagram of the ionic conductivity of the composite solid electrolyte changing with temperature, wherein 0%, 20%, 30%, and 40% correspond to the composite solid electrolytes obtained in the control example, embodiment 3, embodiment 1, and embodiment 4, respectively; Figure 5 It can be seen that under the premise of a film thickness of about 140 μm, at any temperature condition, the ionic conductivity of the embodiment is significantly improved compared with the control example. This is because LLZTO reacts with the polymer chain segment to reduce the crystallinity of the polymer and enhance the Li + migration in the polymer chain; with the increase of temperature, the ionic conductivity of the embodiment further increases.

[0110] Test example

[0111] (1) The composite solid electrolyte prepared in each embodiment is used as the electrolyte to assemble a button cell, wherein the positive electrode active material is lithium iron phosphate, the current collector is aluminum foil, the conductive agent is acetylene black, and the binder is polytetrafluoroethylene (the mass ratio of the positive electrode active material, the conductive agent and the binder is 8:1:1); the negative electrode is metallic lithium. The initial discharge capacity of each button cell at a rate of 0.1C is tested, and then the charge and discharge cycle is performed at 0.1C for 120 cycles, and the discharge capacity after 120 cycles is tested, and the coulombic efficiency is calculated. The coulombic efficiency values ​​of each embodiment are provided as shown in Table 1.

[0112] Further, Figure 6 This is a test diagram of the electrical performance of the button cell prepared in Example 1 of the present invention, wherein: Figure 6 (a) is a room temperature cycle test graph of a button cell obtained in accordance with Example 1. Figure 6 (b) is a charge and discharge curve diagram of the button cell obtained in Example 1 at different cycle numbers at 0.1C. Further, Figure 6(b) provides the discharge characteristic curves at the 1st, 30th, 60th, 90th, and 120th cycles, which correspond to the 1st, 30th, 60th, 90th, and 120th curves in the figure, respectively; Figure 6 (a) and (b) show that at a rate of 0.1C, the initial discharge capacity of the composite solid electrolyte is 153.7 mAh g -1 , and maintained 154.9 mAh g after 120 cycles -1 , and the Coulombic efficiency is 99.7%, indicating that the Li / F-30 / LFP battery assembled with the modified electrolyte membrane has excellent long cycle performance.

[0113] (2) The composite solid electrolyte prepared in each embodiment was used as the electrolyte to assemble a Li / / Li symmetric button cell, in which both the positive and negative electrodes were metallic lithium. By using a lithium foil with a diameter of 16 mm, the -2 At a current density of 1h Li + Electroplating and 1h Li + The stripping cycle was run, and the negative voltage and positive voltage represented the electroplating lithium ions and the stripping lithium ions, respectively. After 2300 h of continuous cycling, the values ​​of the positive voltage and negative voltage at the last cycle were recorded and recorded in Table 1.

[0114] Further, Figure 7 is a cycle stability test curve of the symmetrical battery prepared in Example 1 of the present invention, Figure 7 (a) Figure 7 (b) is the cycle stability curve of the symmetrical battery obtained in Example 1; Figure 7 (a) Corresponding to the change curve of positive and negative voltage during the cycle of 2300 hours (shaded due to the high point density), Figure 7 (b) Corresponding to the change curve of positive and negative voltage during the cycle of 2000 to 2010 hours; the upper and lower limits of the curve indicate that the electrolyte membrane and the lithium negative electrode have excellent interface stability.

[0115] Table 1

[0116]

[0117]

[0118] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A composite solid electrolyte, characterized in that: The composite solid electrolyte is prepared by including the following components in parts by weight: 10-20 parts of inorganic solid electrolyte, 10-20 parts of polyethylene glycol, 10-20 parts of polyethylene oxide, 1-3 parts of cross-linking agent, 10-20 parts of lithium salt and some solvent; Wherein, the cross-linking agent includes isocyanate compounds.

2. The composite solid electrolyte according to claim 1, characterized in that: The inorganic solid electrolyte includes LLZO, Li 10 GeP2S 12 , LLZTO and Li3YBr6.

3. The composite solid electrolyte according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 400 to 4000; And / or, the molecular weight of the polyethylene oxide is 10 5 ~2*10 6 .

4. The composite solid electrolyte according to claim 1, characterized in that: The isocyanate compound includes at least one of 1,3-phenylene diisocyanate, p-phenylene diisocyanate and 3,5-dinitroisocyanate.

5. The composite solid electrolyte according to claim 1, characterized in that: The lithium salt includes at least one of LiPF6, LiClO4, LiTFSI, LiFSI, LiBOB and LiDFOB.

6. The method for preparing a composite solid electrolyte according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: A uniform suspension containing an inorganic solid electrolyte is prepared, and then a cross-linking agent is added to perform a first heat treatment; after the first heat treatment is completed, polyethylene glycol is added to perform a second heat treatment; after the first heat treatment is completed, polyethylene oxide and a lithium salt are added to perform a third heat treatment to obtain a composite slurry; The composite slurry is coated on a support plate, and the support plate is peeled off after drying to obtain a composite solid electrolyte.

7. The method for preparing a composite solid electrolyte according to claim 6, characterized in that: The temperatures of the first heat treatment, the second heat treatment and the third heat treatment are independently 40° C. to 80° C.; The time of the first heat treatment and / or the second heat treatment is 2 hours to 10 hours, and the time of the third heat treatment is 20 hours to 40 hours.

8. The method for preparing a composite solid electrolyte according to claim 6, characterized in that: The drying temperature is 50° C. to 80° C., and the drying time is 20 h to 40 h.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite solid electrolyte according to any one of claims 1 to 5.

10. An electrical device, characterized in that: The electrical device comprises the lithium-ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation and application of organic-inorganic composite solid-state electrolyte

    CN108878959A

  • Organic-inorganic composite solid electrolyte and preparation method and application thereof

    CN110380114A

  • High-safety solid-state electrolyte, preparation method and application thereof

    CN111969245A

  • Ketone group-containing solid polymer electrolyte and battery

    CN113224382A

  • Wide-range temperature electrolyte, preparation thereof and lithium ion battery

    US20210320330A1

Cited By

  • Modified PEO electrolyte membrane and preparation method thereof

    CN121123389A